Hardy apples : growing apples in cold climates - Osborne, Robert A., 1949- (Firefly Books, 2022)
"Hardy Apples is both a practical guide and a loving tribute to the wonderful abundance and diversity of apple cultivars available to the northern gardener and orchardist. Full of tips, facts, beautiful photographs and fascinating stories about apples both popular and obscure, this volume is sure to inform and entertain in equal measure. Drawing on over 40 years of experience propagating and selling apple cultivars from his nursery in Corn Hill, New Brunswick, author Bob Osborne walks you through the basics of how an apple tree grows and the ideal conditions needed to cultivate a successful crop. Osborne also includes vital information about planting, pruning, harvesting, storing, and propagating apples and devotes an entire chapter to preventing and dealing with the pests and diseases that plague so many growers. Following the section on growing apples is an extensive catalog of over 90 apple cultivars. Each profile features a brief history and description of the apple as well as information and photos to help identify cultivars you might already have in your yard. With the growing popularity of hard-cider making, Osborne includes a special section dedicated to excellent cultivars that cideries across North America should seek out. The guide also features North American hardiness zone maps, resources and a handy table of hardy cultivars, a great at-a-glance reference when shopping for trees. With over 200 exquisite photographs and illustrations, Hardy Apples is an elegant, educational and entertaining reference that is equally at home atop a coffee table or a propagator's station."--